Notes on Spintriae from Salona in the Archaeological Museum in Split (Archaeologia Adriatica, 2008)
Spintriae represent a special pseudo-monetary group among tesserae and are made of bronze, brass, copper, lead, bone, glass, or pottery, and are hence of interest primarily to numismatists. On the obverse, spintriae depict an erotic scene between two individuals, and on the reverse, in a laurel wreath with a dotted border a single Roman numeral, from I to XVI, sometimes preceded by the letter A; spintriae where the reverse is different are exceptionally rare, for example with a number greater than XVI, and probably are not authentic. Spintriae are thus erotic tesserae, and the name was given to them by Renaissance antiquarians who knew of such objects as well as the written sources in which spintriae are mentioned, i.e. the works of Suetonius and Tacitus, Twelve Roman Emperors and Annals. Both Suetonius (Twelve Roman Emperors, Tiberius, 43) and Tacitus (Annals, VI. 1), however, use the word spintriae to refer to people. The antiquarians could have seen in the depicted individuals in various sexual poses the emperor’s favorites from the allegations by Suetonius and Tacitus. Champlin in studying the etymology of the word spintria and evaluation of the sources considers that spintriae are those performing group sex, consisting of the participation of three to four men and women, and not, as had been thought, male prostitutes. According to this true spintriae were not depicted on the spintriae. The spintriae depict copulation or fellatio between two individuals, male and female, and more rarely two men.
Keywords: Spintriae; tesserae; erotic scenes; Salona